Streamlining Admissions: Management Information System at Siliwangi Institute of Cimahi - Junaedi, Dedi; Badrudin; Basri, Hasan; Rostandi, Usep Dedi; Fatimah, Siti; Rukanda, Nandang; Kamaludin, Tam-Tam; Hajar, Siti (UIN Sunan Gunung Djati Bandung, 2025)
In the digital era, IKIP Siliwangi Cimahi seeks to enhance educational service quality by improving its new student admission process, which has faced issues like limited information, access difficulties, and data errors. This qualitative case study explores the planning, organization, implementation, supervision, impact, strengths, weaknesses, and design of a management information system (SIM) for admissions, using POAC management, SIM, and academic selection theories. Data were collected via observation, interviews, documentation, and FGD, and analyzed through triangulation. Results show that the SIM is well-structured, improves information access and registration efficiency, and is managed and supervised effectively. Benefits include faster, more transparent admissions, though challenges remain with internet access and occasional technical issues. This study contributes to the field of educational management by providing an in-depth analysis of the development and implementation of a well-structured Management Information System (SIM) for new student admissions at IKIP Siliwangi of Bandung at Cimahi.